The Effect of A Proposed Training Method in Developing Some of the Kinematic Variables of the Throwing and Achievement Stage of the Javelin Effectiveness of the Deaf and Dumb - Taha Hussein , Abbas; Sabeeh Najm, Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to prepare a proposed training approach for the effectiveness of javelin throwing for the deaf and dumb, as well as to identify the impact of the proposed training approach on some kinematic variables of the throwing and achievement phase of the javelin effectiveness of the deaf and dumb. The research fields consisted of the human field for future players of the Deaf and Dumb Forum for the effectiveness of javelin for the sports season 2020 AD and the temporal field for the period from 12/21/2019 to 27/22/2020 either. The spatial field is the Maysan Olympic Stadium scientific method. The researchers used the one-group experimental method to suit the research problem. The research community and sample, as the research community was chosen in the deliberate manner that represented the future forum for the deaf and dumb effectively by throwing a spear in Maysan Province, which numbered eight players. The number of the research sample was six (6) players. Two players were excluded because they were of high achievement, and the percentage was 75% of the original community. Either the most important conclusions. The proposed training curriculum was instrumental in developing the skill of javelin throwing for the deaf and dumb. The most important recommendations the researchers recommend are for the Iraqi deaf and dumb trainers to rely on effective modern training methods and include them in training programs.